Hepatic Steatosis in Patients With Single Ventricle and a Fontan Circulation - Katz, David A. (J Am Heart Assoc, 2021)
BACKGROUND: Hepatic steatosis, caused by nonalcoholic fatty liver disease, is a leading cause of chronic liver disease. The interplay between hepatic steatosis and the development of liver disease following the Fontan procedure is not well understood. This study examined the prevalence and associations of hepatic steatosis in patients with a Fontan circulation. METHODS AND RESULTS: This was a single‐center retrospective study of 95 patients with a Fontan circulation with liver magnetic resonance imaging performed between 2012 and 2019. The average age at magnetic resonance imaging was 21.5±8.5 years. The percent liver fat signal was determined using magnetic resonance chemical shift‐encoded proton density fat fraction imaging. Hepatic steatosis was defined as liver fat ≥5% and was present in 10.5% of the cohort. The presence of hepatic steatosis was associated with higher body mass index (29±4 versus 24±6 kg/m(2), P=0.006), a higher frequency of obesity (50% versus 12%, P=0.015), lower high‐density lipoprotein cholesterol (35±9 versus 43±14 mg/dL, P=0.050), and greater subcutaneous fat thickness (2.6±0.7 versus 1.8±1.0 cm, P=0.043). There was no association between hepatic steatosis and cardiovascular imaging or hemodynamic variables from cardiac catheterization. CONCLUSIONS: Risk factors for hepatic steatosis in patients with Fontan circulation include obesity and dyslipidemia, similar to what is seen in the general population. Fontan hemodynamics were not associated with hepatic steatosis.